EKSPLORASI TANAMAN OBAT POTENSIAL DI KABUPATEN KAMPAR - Zulfahmi Zulfahmi; Bakhendri Solfan (Jurnal Agroteknologi, 2010)
Herbal and aromatic plants are attracting more attention among contemporary plant researchers because some human diseases resulting from bacterial antibiotic resistances have gained worldwide concern. Tropical forests in Kampar district were harboring potential plants genetic resources for herbal medicine, that it was economically potential to develop the next future. Presently, the information on potential plants genetic resources for herbal medicine is unknown. The objective of this research was to explore the plants genetic resources of herbal medicine in Kampar district. The result of exploration was found 32 species potential for herbal medicinal and aromatic. Most of them have been cultivated by society as house garden, but partially growth in nature wild. Local people have used as traditional medicine in decade. A part of potential plant was found difficult due to occur the heavy harvesting by society and conservation required